The Political Ecology of a Highway through Belize's Forested Borderlands. (April 2015) - Wainwright, Joel; Jiang, Shiguo; Mercer, Kristin; Liu, Desheng
This paper examines how a new highway in Belize will change a tropical forest landscape. Since the end of British colonialism (1981), the Maya communities in Belize's Toledo District have struggled with the state for control of the lands they have customarily used to produce a livelihood. We were approached by some Maya leaders, who recognize that the paving of a new highway through their villages could transform Maya agricultural practices and thus land use and cover change (LUCC), and asked to produce an analysis that could assist them in managing their lands. We braid together historical, social, political, economic, and satellite data to answer two questions: (1) How has land cover changed since 1975 in areas with Maya customary versus noncustomary land-use practices? (2) What will be the consequences of paving the new highway through this region for the landscape and the Maya communities? Using a multifaceted LUCC/political ecology analysis we found that forest clearing is greatest where noncustomary farming practices are employed. Noncustomary practices are spatially concentrated along the Belize-Guatemala border; the shift to noncustomary practices resulted from inmigration by war refugees who maintained close ties to Guatemalan markets. The paving of the highway promises to reduce the functional distance to Guatemala's markets, which could change land use in other villages to the detriment of the forests because of the likely diffusion of noncustomary farm practices. Forest change will be shaped by the region's complex political geography.